A Numerical Approach to Determine Attitude Dynamics of Floating Bodies with Irregular Configurations. (16th July 2014) - Chen, Jiann-Lin; Chu, Li-Ming; Wen, Chan-Chuan
Abstract : This study acquires the attitude dynamics of floating bodies with irregular configurations using an effective computational model, which has been validated theoretically and verified by experiments. By comparison a correlation formula was described to predict inclinations for the floating slender body imitating an excise torpedo. Thereafter a computational model was developed to account for bodies with attitudes in more general situations. For demonstration, a submersible was simulated to reveal that the inclinations vary abruptly around certain longitudinal locations of center of gravity. The property variations during water ingress assumption were presented. Similar to the virtue tank, an innovative concept of building the numerical data base for a specific floating body has been proposed, by which the position of its center of gravity can be obtained by interpolation from attitude data in tables as determined by the present computational model.